2022
DOI: 10.32322/jhsm.1056614
|View full text |Cite
|
Sign up to set email alerts
|

Platelet-lymphocyte ratio predicts poor prognosis in stage II/III colon and rectum cancer

Abstract: Objective: There is an increasing number of studies in the literature reporting that serum platelet/lymphocyte ratio (PLR) can provide useful prognostic data for various cancers. In the present study, the effects of platelet-lymphocyte ratio on survival in stage II/III colorectal cancers (CRC) were examined. Material and Method:A total of 106 Stage II/III CRC patients who underwent curative surgery 2015-2020 were included in the study. Emergency cases and patients diagnosed with other than adenocarcinoma were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…Recently, Benek et al. demonstrated that elevated PDW was associated with poorer OS in CRC patients 34 . Similarly, Song et al.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Recently, Benek et al. demonstrated that elevated PDW was associated with poorer OS in CRC patients 34 . Similarly, Song et al.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, Benek et al demonstrated that elevated PDW was associated with poorer OS in CRC patients. 34 Similarly, Song et al showed that increasing PDW was associated with worse OS in non-metastatic CRC patients. 35 On the other hand, Qian et al revealed that preoperative PDW does not correlate with patient outcomes.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation